The Inefficiency of Employment and the Case for Workplace Democracy - Felix FitzRoy; Michael A. Nolan (Institute of Labor Economics (IZA), 2021)
While most working people are in employment, there is little realisation that this relationship is inefficient and inequitable due to mis-aligned incentives – employers, as residual claimants, have an incentive to elicit greater than socially optimal effort from workers, thus generating conflict and exploitation, while workers have no 'voice' and 'exit' is costly. Workplace democracy combines efficiency and equity, aligning incentives and giving workers their natural right of self-determination, but is relatively rare due to the historically constructed power of concentrated capital owners. We show how workplace democracy can be established without expropriating capital owners, yielding efficiency and welfare gains.
Keywords: J; 330; employment; workplace democracy